Trends and future outlooks in circularity of desalination membrane materials - Liang, Yuanzhe; Knauer, Katrina M. (Frontiers in Membrane Science and Technology, 2023)
Reverse osmosis desalination is one of the most important and increasingly popular technologies to augment available water resources. Central to the technology is a thin-film-composite polyamide membrane capable of separating pure water from seawater or brine. Since its conception and initiation, the membrane industry has followed a linear life-cycle scheme. However, increasing production costs of fossil-based materials and more stringent environmental regulations drive the initiatives to adapt to a circular economy of membrane materials. In this perspective, we briefly summarize the pressing issues in the state-of-the-art membrane industry, then discuss the opportunities in future technology innovations with a focus on sustainable membrane manufacturing and recycling, and lastly provided an outlook for future membrane design and fabrication towards a circular economy.